Genomic Analyses of Methicillin-Resistant Staphylococcus pseudintermedius from Companion Animals Reveal Changing Clonal Populations, Multidrug Resistance, and Virulence - Mattias Myrenås; Karl Pedersen; Ulrika Windahl (MDPI AG, 2024)
Background/Objectives: Staphylococcus pseudintermedius is part of the normal microbiota in dogs. Since 2006, an increase in multidrug-resistant clones of methicillin-resistant S. pseudintermedius has been reported, as well as zoonotic transmission. Longitudinal investigations into clonal population structures, antibiotic resistance patterns, and the presence of resistance and virulence genes are important tools for gaining knowledge of the mechanisms behind the emergence of such clones. Methods: We investigated 87% of all non-repetitive MRSP isolates from dogs and cats in Sweden over a ten-year period (n = 356). All isolates were subjected to staphylococcal chromosomal cassette mec identification, whole-genome sequencing, multi-locus sequence typing, and analyses of genomic relatedness, as well as investigation of phenotypical resistance patterns and the presence of antibiotic resistance genes and virulence genes. Results: A considerable increase over time in the number of clonal lineages present was observed, indicating genomic diversification, and four clones became dominant: ST71, ST258, ST265, and ST551. In total, 96% of the isolates were multidrug-resistant. Statistically significant differences in resistance to several antibiotic classes between the four dominant clones were present. All isolates carried several virulence genes encoding factors associated with attachment, colonization, toxin synthesis, quorum sensing, antibiotic resistance, and immune evasion.